Aberrant self-renewal and quiescence contribute to the aggressiveness of glioblastoma - Campos, Benito; Gál, Zoltán; Baader, Aline; Schneider, Tilman Georg Rudolph; Sliwinski, Christopher; Gassel, Kristina Maria; Bageritz, Josephine; Grabe, Niels; Deimling, Andreas von; Beckhove, Philipp; Mogler, Carolin; Goidts, Violaine; et al. (The journal of pathology, 2014)
Cancer cells with enhanced self-renewal capacity influence tumour growth in glioblastoma. So far, a variety of surrogate markers have been proposed to enrich these cells, emphasizing the need to devise new characterization methods. Here, we screen a large panel of glioblastoma cultures (n = 21) cultivated under stem cell-permissive conditions and identify several cell lines with enhanced self-renewal capacity. These cell lines are capable of matrix-independent growth and form fast-growing, orthotopic tumours in mice. Employing isolation, re-plating, and label-retention techniques, we show that self-renewal potential of individual cells is partitioned asymmetrically between daughter cells in a robust and cell line-specific fashion. This yields populations of fast- and slow-cycling cells, which differ in the expression of cell cycle-associated transcripts. Intriguingly, fast-growing cells keep their slow-cycling counterparts in a reversible state of quiescence associated with high chemoresistance. Our results suggest that two different subpopulations of tumour cells contribute to aberrant growth and tumour recurrence after therapy in glioblastoma. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Gesehen am 24.07.2020